The Effect of Implementing the Project Based Learning (PJBL) Learning Model on Critical Thinking Skills in Science Learning for Grade 4 Students of SD Negeri 30 Pasir Tuntung - Rita Harisma; Melyani Sari Sitepu; Halimah Tussa’diah; Lhutfia Wahyu Safutri (Lembaga Bale Literasi, 2026)
This study aims to describe the effect of implementing project-based learning (PjBL) models on critical thinking skills in 4th grade elementary school students. This study uses a quantitative approach with a pretest-posttest one group design. Data were collected through tests to measure students' critical thinking skills. Data analysis techniques include normality tests and Paired Sample t-Test tests. The results of the study showed an increase in students' critical thinking skills after the implementation of project-based learning models. The average pretest score of 50.5 increased to 70.5 in the posttest. The results of the Paired Sample t-Test test showed a significance value of 0.000 (<0.05), so it can be concluded that there is a significant influence between the implementation of project-based learning models on students' critical thinking skills. Thus, the project-based learning model is effective for improving the critical thinking skills of 4th grade students of SD Negeri 30 Pasir Tuntung.